Implementasi Permendagri N0 113 Tahun 2014 dalam APBDesa - Pratama, Athar Yaniar; Br. Sebayang, Lesta Lesta Karolina (Efficient: Indonesian Journal of Development Economics, 2018)
This study aims to examine and find out the implementation of Permendagri No. 113 of 2014 in Ngesrepbalong Village, Limbangan, Kendal Regency and analyze the obstacles faced by village officials in its implementation.This study uses a qualitative approach with a case study research strategy. Data obtained through interviews and documentation studies.The results of the study show the Implementation of Permendagri No. 113 of 2014 in Ngesrepbalong Village can generally be seen from the following findings: Fund allocation is not appropriate in accordance with the provisions; There is a discrepancy between the list of program activities that have been agreed upon in the village meeting with the details of the activities contained in the RKP table; There is an RKP that does not include a discussion on the evaluation of the previous year's financial use; in the aspect of transparency, the Village Government has implemented it by informing the allocation of funds and the development of their use on information boards in the village office. Penelitian ini bertujuan untuk mengkaji dan mengetahui implementasi Permendagri No 113 tahun 2014 di Desa Ngesrepbalong Kecamatan Limbangan Kabupaten Kendal dan menganalisis kendala yang dihadapi aparatur desa dalam pelaksanaannya.Penelitian ini menggunakan pendekatan kualitatif dengan strategi penelitian studi kasus. Data yang diperoleh melalui wawancara dan studi dokumentasi. Hasil penelitian menunjukkan Implementasi Permendagri No 113 tahun 2014 di Desa Ngesrepbalong dapat dilihat dari temuan berikut ini: Pengalokasian dana tidak tepat sesuai dengan ketentuan; Adanya ketidaksesuaian antara daftar program kegiatan yang telah disepakai dalam musyawarah desa dengan rincian kegiatan yang ada dalam tabel RKP; Terdapat RKP yang tidak mencantumkan pembahasan mengenai evaluasi penggunaan keuangan tahun sebelumnya; pada aspek trasnparansi, Pemerintah Desa telah melaksanakannya dengan menginformasikan pengalokasian dana dan perkembangan penggunaannya pada papan informasi di kantor desa.